Biogenesis of thylakoid membranes is controlled by light intensity in the conditional chlorophyll b-deficient CD3 mutant of wheat (The Rockefeller University Press, 1988)
Biogenesis of thylakoid membranes in the conditional chlorophyll b- deficient CD3 mutant of wheat is dramatically altered by relatively small differences in the light intensity under which seedlings are grown. When the CD3 mutant is grown at 400 microE/m2 S (high light, about one-fifth full sunlight) plants are deficient in chlorophyll b (chlorophyll a/b ratio greater than 6.0) and lack or contain greatly reduced amounts of the chlorophyll a/b-binding complexes CPII/CPII (mobile or peripheral LHCII), CP29, CP24 and LHCI, as shown by mildly denaturing 'green gel' electrophoresis, by fully denaturing SDS-PAGE, and by Western blot analysis. High light CD3 chloroplasts display an unusual morphology characterized by large, sheet-like stromal thylakoids formed into parallel unstacked arrays and a limited number of small grana stacks displaced toward the edges of the arrays. Changes in the supramolecular organization of CD3 thylakoids, seen with freeze- fracture electron microscopy, include a reduction in the size of EFs particles, which correspond to photosystem II centers with variable amounts of attached LHCII, and a redistribution of EF particles from the stacked to the unstacked regions. When CD3 seedlings are grown at 150 microE/m2 S (low light) there is a substantial reversal of all of these effects. Thus, chlorophyll b and the chlorophyll a/b-binding proteins accumulate to near wild-type levels (chlorophyll a/b ratio = 3.5-4.5) and thylakoid morphology is more nearly wild type in appearance. Growth of the CD3 mutant in the presence of chloramphenicol stimulates the accumulation of chlorophyll b and its binding proteins (Duysen, M. E., T. P. Freeman, N. D. Williams, and L. L. Huckle. 1985. Plant Physiol. 78:531-536). We show that this partial rescue of the CD3 high light phenotype is accompanied by large changes in thylakoid structure. The CD3 mutant, which defines a new class of chlorophyll b- deficient phenotype, is discussed in the more general context of chlorophyll b deficiency.